NEW TECHNOLOGIES IN EDUCATION - HRBACEK, Jiri (Trends in education, 2010)
The article deals with basic possibilities of using new technologies in education, especially in education of technical subjects. This article demonstrates possibilities of implementation of MyIMLE system, which is being developed at our department, to this education.
Keywords: MyIMLE; technical education; education; study supports with internal intelligence.